The Contest for Aboriginal Souls European missionary agendas in Australia - Ganter, Regina (ANU Press, 2018)
"This book covers the missionary activity in Australia conducted by non-English speaking missionaries from Catholic and Protestant mission societies from its beginnings to the end of the mission era. It looks through the eyes of the missionaries and their helpers, as well as incorporating Indigenous perspectives and offering a balanced assessment of missionary endeavour in Australia, attuned to the controversies that surround mission history. It means neither to condemn nor praise, but rather to understand the various responses of Indigenous communities, the intentions of missionaries, the agendas of the mission societies and the many tensions besetting the mission endeavour. It explores a common commitment to the supernatural and the role of intermediaries like local diplomats and evangelists from the Pacific Islands and Philippines, and emphasises the strong role played by non-English speakers in the transcultural Australian mission effort. This book is a companion to the website German Missionaries in Australia - A web-directory of intercultural encounters. The web-directory provides detailed accounts of Australian missions staffed with German speakers. The book reads laterally across the different missions and produces a completely different type of knowledge about missions. The book and its accompanying website are based on a decade of research ranging across mission archives with foreign-language sources that have not previously been accessed for a historiography of Australian missions. 'A remarkable intellectual achievement, compelling reading.' - Dr Niel Gunson 'The range of knowledge on display here is very impressive indeed.' - Professor Peter Monteath"